2014
DOI: 10.1089/tmj.2014.0026
|View full text |Cite
|
Sign up to set email alerts
|

Cabo Verde Telemedicine Program: Initial Results of Nationwide Implementation

Abstract: The ITeHP-CV has been successfully launched, and the initial results are encouraging. The continuity of the program and sustainability are primary goals once the program is transferred fully to the Ministry of Health of Cabo Verde. A long-term follow-up study is required in order to ensure sustainability and continuity goals are met.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…Provider (e.g., clinicians and nurses) participation in the planning and design of the system was a major contributor to successful implementation, partly because it facilitated ownership of the program during the planning stage [59]. Article numbers presented in this table aligns with the studies identified in this review listed in Table 2 Gain leadership and management support and commitment In 31 % (N = 15/48) of studies, leadership or management support and commitment were identified as vital factors for success and sustainability [55,58,76].…”
Section: Main Characteristics Of the Selected Articles In Reviewmentioning
confidence: 66%
See 1 more Smart Citation
“…Provider (e.g., clinicians and nurses) participation in the planning and design of the system was a major contributor to successful implementation, partly because it facilitated ownership of the program during the planning stage [59]. Article numbers presented in this table aligns with the studies identified in this review listed in Table 2 Gain leadership and management support and commitment In 31 % (N = 15/48) of studies, leadership or management support and commitment were identified as vital factors for success and sustainability [55,58,76].…”
Section: Main Characteristics Of the Selected Articles In Reviewmentioning
confidence: 66%
“…A little under a third (N = 15/48) of the studies in our review reported that telemedicine champions are essential to securing successful telemedicine participation and uptake. These telemedicine champions played a role in promoting (e.g., awareness and education through example) [37,55] and legitimized telemedicine, as well as building relationships with various stakeholders [58,59,74]. Selecting key staff members who were willing to actively participate in telemedicine programs and fundamentally believe in the concept of telemedicine was found to influence other people as well as support buy-in [59].…”
Section: Main Characteristics Of the Selected Articles In Reviewmentioning
confidence: 99%
“…3 This model has been successfully utilized to establish telemedicine and e-health education services in other countries both in the Balkans region and in Africa. [4][5][6][7] Currently, the Albanian program is in the last phase or Transfer phase, the final element of the IBOT strategy.…”
mentioning
confidence: 99%
“…The emergence of Information and Communication Technology (ICT) in the health sector brings innovative changes which increased the effectiveness of healthcare services. Those include patients' health monitoring technologies like wearables devices (Ghamari et al 2016), use of robotics, tele-medicine, online consultation, and health management applications (Latifi et al 2014;Khosravi and Ghapanchi 2016 brings positive changes worldwide, while on the other hand, widespread use of technology in everyday life brings detrimental effects on a global scale especially among the youth. Many studies report excessive use of smartphone and video games among youngsters lead to depression, anxiety, poor academic performance, and lack of attention (Craparo 2011;Brunborg et al 2014;Cutino and Nees 2017;Rozgonjuk et al 2018).…”
Section: Discussionmentioning
confidence: 99%